USE OF CULTURE-SPECIFIC ITEMS AND THEIR TRANSLATION FROM LITHUANIAN INTO ENGLISH AND FRENCH IN RIČARDAS GAVELIS’S VILNIUS POKER - Leonavičienė, Aurelija; Inokaitytė, Gintarė (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
From the beginnings of translation studies to the present day, the theoretical and practical paradigm of translation has come a long way. Although it was closely associated with linguistics and the solution of linguistic problems of translation until the early 1980s, it was the first translation theories that drew attention to the cultural phenomena of texts and the challenges of translation. Translation scholars Susan Bassnett and André Lefevre (1990) wrote that translation’s shift to cultural phenomena represented a significant cultural turn. This led to a paradigm shift in translation and a new view that translation is an intercultural act and a dialogue between cultures. Given the importance and relevance of research on cultural meanings in translation, this paper focuses on one type of cultural meanings – culture-specific items that sometimes become a cultural stumbling block for translators. The aim of the research described in the article is to analyse the peculiarities of the use of culture-specific items in Ričardas Gavelis’s novel Vilnius Poker, to conduct a comparative study of the translation of culture-specific items from Lithuanian into English and French, and to determine the translation techniques, strategies and trends of cultural transposition used by translators. The methods used to achieve the aim of the study include synthesis of scientific literature, comparative, descriptive and quantitative analysis. The use and translation of culture-specific items does not raise the issue of equivalence and linguistic deficit. Culture-specific items are analysed not as a separate unit of the text, but as part of a holistic whole that is organically integrated into the text and contributes to its meaning. The use of culture-specific items in the research material has led to the identification of four thematic groups: social, political, and historical; folkloric and mythological; domestic; and geographical. The data obtained in the quantitative use of culture-specific items suggest that two-fifths of all the culture-specific items analysed belong to the social, political, and historical thematic group reflecting the social life, deformations, Soviet experiences, and worldview of the people in the Soviet period in Vilnius and Lithuania as a whole, as portrayed by R. Gavelis. In a comparative study of translating culture-specific items from Lithuanian into English and French, based on the translation techniques and strategies described by Andrew Chesterman, nine translation techniques and three strategies were identified: from the semantic translation strategy, synonymy, abstraction change, trope change, and paraphrase were used; from the pragmatic translation strategy, the techniques of translation were: explicitness change and omission; from the syntactic or change of form translation, the translation techniques were: literal translation, loan, and transposition. The evaluation of the different translation techniques chosen by the English and French translators to translate culture-specific items showed that the English translation adopted the tendency of foreignization in order to “bring the reader to the author”, i.e. to provide the readers of the translation with as much systematic cultural information as possible about Soviet and postwar Lithuania. In contrast, French translation showed the opposite tendency toward domestication, i.e. the abandonment, omission, or replacement of certain cultural meanings with French cultural meanings. In this, the translator’s cultural transposition was shown to “bring the author to the reader”.